Marketing-Sales Interface and Organizational Competitiveness - Avlonitis George J.; Lionakis Konstantinos (Marketing of Scientific and Research Organizations, 2015)
This paper focuses on the effectiveness of marketing-sales interfaces in B2B firms. As the body of knowledge on this domain is scarce, there is a greater need to investigate the specific aspects of marketing-sales configurations in such firms. The objective of this paper is to expand existing knowledge regarding marketing-sales interfaces in B2B firms, in order to identify the effectiveness of each configuration. Based on quantitative data collected from marketing or sales managers of 98 B2B firms, the study identifies the most effective marketing-sales interface in terms of smooth relationships and enhanced performance. The implications of the study are discussed.